Employee retention and organizational performance: Evidence from Ghana Police Service - Opare Darko, Irene Lawrencia; Bans-Akutey, Anita; Amoako, Patricia; Affum, Lydia Kyerewa (goodwood publishing, 2024)
Purpose: This study examined workplace factors that influence employees’ stay, the importance of employee retention practices, and the influence of employee retention on organizational performance. Research Methodology: It study used a quantitative approach and a case study strategy. The study population included selected staff from three (3) departments at the Accra Regional Headquarters of the Ghana Police Service. Participants were randomly selected to complete the self-administered questionnaires. Results were analyzed using descriptive statistics and are presented in tables. Results: The work environment, competitive compensation and benefits, organizational culture, and personal development opportunities are factors that affect employee retention. It was also found that employee retention enhances the stability and continuous progress of employees, improves employee morale, attracts and retains top talent, and increases job satisfaction. Finally, employee retention positively influences organizational performance by increasing efficiency and productivity, knowledge retention, and financial performance. Limitations: This study was limited to employees at the Regional Headquarters of the Ghana Police Service, a government institution. Contribution: Organizations need to create a respectful, inclusive, and supportive workplace that improves retention. Attractive remuneration frameworks that retain skilled officers and personnel should also be adopted. It is also important to explore employee career advancement pathways. Novelty: This study focuses on the influence of employee retention on organizational performance in a service-oriented government institution.